MANAJEMEN PRODUKSI PROGRAM SIARAN “KAMPUNG RADIO” RADIO REPUBLIK INDONESIA PRO 1 PEKANBARU DALAM PEMBERDAYAAN MASYARAKAT KOTA PEKANBARU - Rizki Widiyawati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Radio Republik Indonesia (RRI) Programa 1 Pekanbaru has popular program of community empowerment that is Kampung Radio. by the strong competition and rapid development of society, RRI seeks to present information about the problems and potentials that exist in the community environment, with expecation of society to more sensitive and get the initiative to become a more independent society. Thus this study aims to find out how the management of production on broadcasting Kampung Radio of Radio Republik Indonesia Pro 1 Pekanbaru in empowering the society of Pekanbaru.This research uses qualitative method. The object of research is the production management program broadcast kampung radio of radio republic Indonesia pro 1 Pekanbaru in empowering people of Pekanbaru city. Research subjects consist of planning team, show director, presenter and two listeners or community involved in production, determined by purposive sampling method. Data collection techniques used are observation, interview and documentation.The results of this study show that RRI implements 4 stages in production management of broadcast radio program, First, Planning, including location planning, content / topic planning and cost planning. Second, Organizing. For all working relatives in charge placed in accordance with their respective expertise. Thirdly, Actuating is the whole work relative in accordance with the task specified in the program meeting. Fourth, Controlling. The supervision is divided into three phases: initial supervision conducted before broadcasting, middle supervision, supervision during broadcasting and final supervision. All series of processes is a form of production management process of broadcasting of radio program in the empowerment of urban community Pekanbaru.Keywords: Management, Radio, Production, Broadcasting